Analisis Faktor yang Berhubungan dengan Tingkat Demensia Pada Lansia di Panti Jompo Harapan Kita Kota Palembang: Penelitian - Sherly Widianti; Dessy Purwanti (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Dementia is often called senility which is not a normal part of aging, which needs special attention because it has a broad impact on the physical condition, well-being of the elderly and their families. This study aims to determine the relationship between age, gender, and education with the level of dementia in the elderly. This research method is quantitative analytic with a cross-sectional approach. The sample in this study was the elderly with dementia as many as 48 samples using the purposive sampling method. The study was conducted on May 1 - May 30, 2025 at the Harapan Kita nursing home in Palembang City. The results showed a significant relationship between age (p = 0.001), gender (p = 0.016), and education level (p = 0.026) with the level of dementia in the elderly at the Harapan Kita Nursing Home in Palembang. It is recommended that nursing homes improve monitoring of dementia risk factors, and further researchers can examine other variables such as medical history and lifestyle to obtain a more comprehensive picture.